Analisis Perbandingan Kinerja Keuangan Sebelum dan Sesudah Pandemi Covid-19 pada Pemerintah Daerah Kabupaten Gresik - Pingkan Ardhana Rheswari; Fajar Syaiful Akbar (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This study aims to test and analyze comparisons of financial performance before and after the Covid-19 pandemic in the gresik district government. The population used in this study is the financial data of the Gresik Regency government located in the province of East Java. This research is quantitative descriptive research. This study uses secondary data in the form of budget realization reports. Sampling techniques use documentation methods. Analytical techniques in this study use quantitative descriptive analysis. The results of this study show that the effectiveness ratio of PAD with an average of 104% is already classified as very effective, the ratio of regional financial independence with an average of 251% is already included in the pattern of participatory relations, the ratio of fiscal decentralization degrees is on average 32% and has been included in the category quite well. The average compatibility ratio of operating expenditure is 75% and capital expenditure is 11%. An average financial efficiency ratio of 84% is already quite efficient. Keywords: effectiveness ratio of PAD; regional financial independence ratio; fiscal decentralization degrees ratio; operating expenditure ratio; financial efficiency ratio